Experience of using the biodestructor Devoroil for cleaning soils of railway sections from oil contaminations - Gorovykh, Olga G.; Budko, Sviatlana V.; Saevich, Konstantin F. (Journal of the Belarusian State University. Ecology, 2022)
The actual environmental problem of pollution of the territories of the Belarusian Railway organizations by oil products is considered. The grounds for choosing the drug «Devoroil» for cleaning contaminated areas from weathered and bituminized oil products are considered. The results of studies of the content of oil products in the territory of the structural subdivisions of the Brest branch of the Belarusian Railway are given, pollution reached a value of 84900 mg oil products/soil. It is noted that the most polluted are the soils between the sleepers of individual tracks. Bioremediation studies were carried out both on a special site (ex situ) and directly at the site of contamination (in situ). Soils contaminated with oil products were disinfected using the Devoroil biodestructor in the spring-autumn period for six years. It has been established that in one spring-autumn period, the decrease in the content of oil products in oil-contaminated soils can reach 90 %. However, the achievement of MPC standards, even with an increase in the content of the Devoroil preparation and a double treatment during one season, was not achieved.
Keywords: oil pollution; soil; biodegradants